An analysis of administrative staff’s participatory decision making through syura at international Islamic tertiary institution - Salleh, Mohamad Johdi; Abdulwahab Al-Daba, Abdulmajid Mohamed (Academicians' Research Center (ARC), 2014)
The objective of the study is to investigate the administrative staff’s participation in decision-making through the principle of Shura or consultation at International Islamic Tertiary Education Institution. The study involved purposive sampling of 255 non-academic administrative staff at the International Islamic University Malaysia (IIUM) from all Kulliyyahs, Centres, and, Divisions. This research used a set of survey questionnaire as means of gathering data on participatory decision-making among respondents. The Statistical Package for Social Science (SPSS) version 20 was used to organize and summarize the information gathered since the nature of research is exploratory. The result of the study shows that the highest percentage for the all five items in the scale is “Mostly” which is 37.56% followed by “Often” which is 34.04% then average mean of “Always” is 13.16%. This is followed by “Occasionally” with 10.98% and the last is “Never” that recorded 4.24%. However, the average mean score to all the 5 items is 3.44 and Standard Deviation is 0.992 which indicate that the system of Shura was implemented and the majority of the staff participated in the decision-making through the system of Shura at IIUM. The high participation of staff in decision making may improve the employer-employee relationships, enhances productivity, effective administration and promotes transparent, accountability and good governance in the organization.